A Legal and Social Study of the Limited Capacity Institute Using an Ecological Systems Theory Approach - Genienė, Rasa; Krutulytė, Kornelija (Socialinė teorija, empirija, politika ir praktika, 2025)
The problem of legal incapacity is actualized by the pressure of disability rights activists to implement the accepted international obligations of the country in order to ensure the implementation of legal capacity of persons with disabilities. Using the approach of ecological systems theory, this article deconstructs the system of (non)restriction of legal capacity of a person, in which the roles and power positions of different sectors (social, health care, justice) interact. The article reveals that the implementation of incapacity reform requires changes at all levels of the system, starting from the person's immediate environment (mico level), the interaction of service-providing organizations and specialists (meso level), changing rules and behavior (meso level), changes in the legal system (macro level).
Keywords: legal capacity; incapacity reform; intellectual and/or psychosocial disability; ecological systems theory; supported decision making